Studi Teoritis Karakteristik Termal Pembakaran Biomassa Tanaman Energi pada Berbagai Kondisi Udara dalam Tungku Adiabatik - Haris Mawardi; Edy Hartulistiyoso; Muhamad Yulianto (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Combustion is an energy conversion method involving the reaction of fuel and oxygen to generate heat. Coal remains predominant in Indonesia’s energy mix, contributing to over 50% of global CO2 emissions. Efforts to reduce these emissions include using renewable energy sources like biomass, with current potential in energy crop biomass such as gamal and sengon wood. However, the thermal characteristics of burning gamal and sengon wood have not been extensively studied. This paper discusses the theoretical thermal characteristics of gamal and sengon wood combustion through numerical simulation using a combustion equilibrium model in an adiabatic furnace under stoichiometric, excess air, and excess fuel conditions. Thermodynamic calculations will be validated against experimental data. The simulation results show that the thermal characteristics of gamal combustion are superior to those of sengon. Adjustments in air supply can impact combustion quality, where excess air is often necessary to mitigate environmental factors disrupting theoretical stoichiometric combustion. Optimal combustion conditions are achieved at equivalence ratios of 1.3 for gamal and sengon. Validation using Mean Absolute Percentage Error (MAPE) indicates low error values (8,55%) affirming the model’s ability to predict thermal characteristics accurately.